Commodity Price Volatility and the Use of Derivatives for Risk Mitigation - Bakoeva Gulbakhor (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Commodity price volatility poses significant risks for producers, consumers, and investors across global markets. Factors such as geopolitical tensions, weather changes, supply chain disruptions, and speculative trading contribute to unpredictable fluctuations in commodity prices. Derivative instruments—such as futures, options, forwards, and swaps—play a central role in mitigating these risks. This paper examines the causes and consequences of commodity price volatility, explores how derivatives function as risk management tools, and provides real-world evidence from agricultural, energy, and metals markets. It concludes with an analysis of the benefits and limitations of derivatives in stabilizing earnings, ensuring financial predictability, and promoting sustainable growth in commodity-dependent sectors.